1996
DOI: 10.1111/j.1467-6494.1996.tb00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Coping: Three Generations of Research

Abstract: This article introduces the Journal of Personality's special issue on coping and personality. It first presents a historical overview of the psychological study of how people cope with stress and identifies three generations of theory and research: (a) the psychoanalysts and the ego development school, which tended to equate personality and coping strategies; (b) the transactional approach, which appeared in the 1960s and emphasized situational and cognitive influences on coping while downplaying the role of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
22

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(113 citation statements)
references
References 114 publications
3
88
0
22
Order By: Relevance
“…As in the case of self-evaluative cognitions, it is also crucial to focus on the timing of coping. We need to consider which coping behavior is exhibited at which point in the coping process (e.g., Suls, David, & Harvey, 1996). For instance, longitudinal studies in the domain of coping with cancer (e.g., Filipp, 1999) and with death of a close person (e.g., Wortman & Silver, 2001) demonstrated that coping strategies such as "minimizing the threat " and " wish for someone to take over " maintained their adaptive power across a period of 9 months after the critical event.…”
Section: Coping and Control Strategies: Further Evidence For Reserve mentioning
confidence: 99%
“…As in the case of self-evaluative cognitions, it is also crucial to focus on the timing of coping. We need to consider which coping behavior is exhibited at which point in the coping process (e.g., Suls, David, & Harvey, 1996). For instance, longitudinal studies in the domain of coping with cancer (e.g., Filipp, 1999) and with death of a close person (e.g., Wortman & Silver, 2001) demonstrated that coping strategies such as "minimizing the threat " and " wish for someone to take over " maintained their adaptive power across a period of 9 months after the critical event.…”
Section: Coping and Control Strategies: Further Evidence For Reserve mentioning
confidence: 99%
“…Personality and coping were essentially equated in psychodynamic theory, with defense mechanisms conceptualized as stable traits that influenced perceptions of events and dictated consistently adaptive or maladaptive responses (see Suls, David, & Harvey, 1996, for an excellent history). Although most researchers now distinguish between personality and coping, some conceptualizations of coping remain quite broad.…”
Section: Defining Personality and Copingmentioning
confidence: 99%
“…Contemporary stress research grew out of an older, psychodynamicoriented literature that emphasized the importance of ego defenses as mechanisms for adapting to stress and anxiety, which led to the emergence of trait-theories of stress (Suls et al, 1996). Empirical support for the ego defense perspective consisted largely of case studies and failed to provide a distinction between defense mechanisms and outcomes (Suls et al, 1996).…”
Section: Theoretical Perspectives On Stress Trait Perspectivementioning
confidence: 99%